A Model of Rationality: The Perspective of Utility in Social Policies - Gabriela Rățulea (Argumentum: Journal of the Seminar of Discursive Logic, Argumentation Theory and Rhetoric, 2021)
This paper aims to show that utilitarianism remains the essential way to justify social policies, despite the criticisms received from deontological approaches. Two questions are of interest: one of them concerns the utilitarian roots of social reforms which have led to the improvement of the situation of disadvantaged people; the other concerns the type of answers that can be given in order to maintain the utilitarian position. If we analyse the distinction between utilitarianism of action and utilitarianism of rules, we can understand that there is a kind of cunning of utilitarian reason which makes it possible to achieve maximization of general utility without directly seeking this goal. It would then be possible to extend this view and consider in the same way the unavoidable question of universal rights and obligations (that are concepts from the opposite approach). Thus, we can admit that some non-utilitarian principles of moral action can be inserted into the general logic of the production of happiness, in order to obtain mixed criteria of decision.